Nitrogen fertilisation efficiency and wheat grain yield affected by nitrogen doses and sources associated with Azospirillum brasilense - Fernando Shintate Galindo; Marcelo Carvalho Minhoto Teixeira Filho; Salatiér Buzetti; Willian Lima Rodrigues; José Mateus Kondo Santini; Cleiton José Alves (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2019)
The nitrogen fertilisation management should focus on increasing fertilisation efficiency in favour of a more sustainable and productive agriculture. Thus, this study aimed to evaluate the effect of inoculation with Azospirillum brasilense, associated to N doses and sources, in Savannah conditions, on agronomic efficiency (AE), recovery of applied nitrogen (RAN), physiological efficiency (PE), agrophysiological efficiency (AGREC), nitrogen use efficiency (NUE), nitrogen harvest index (NHI) and wheat grain yield. The experiment was developed in a Rhodic Hapludox soil under no-tillage system. The experimental design was a randomised complete block design with four replicates arranged in a 2 × 5×2 factorial scheme: Two N sources [(urea and urea with inhibitor of the enzyme NBPT (N – (n – butyl thiophosphoric) Triamide))], five N doses applied in top-dressing (0, 50, 100, 150 and 200 kg ha−1), with and without inoculation with A. brasilense. The increase in N doses reduced the nitrogen fertilisation efficiency. No significant differences were observed among the N sources. Inoculation increased the AE of nitrogen sources and can increase RAN. The increase in N dose up to 140 kg ha−1 associated with inoculation increased wheat grain yield.